THE EFFECTS OF BRANCHED-CHAIN AMINO ACIDS (BCAA) SUPPLEMENTATION - Gomes de Abreu, Jonatas; Iranley Santos Luna, José; dias Cavalcante Abreu, Dandara; Emanoel de Abreu Oliveira, Pierri; Alves Moreira, Jéssica (Health and Society, 2023)
Introduction: BCAA branched-chain amino acid supplementation is a process highly sought after by people who wish to gain muscle mass. These amino acids act as an important source of energy for skeletal muscle during periods of metabolic stress. In line with this, BCAAs play a crucial role in promoting protein synthesis in order to prevent protein catabolism and serve as a reserve for the gluconeogenesis process. Therefore, the importance of research on the effects of branched-chain amino acid supplementation is of fundamental importance so that the main indications and effects that this supplementation can cause can be understood. In this step, the relevance of the research is corroborated due to the need for knowledge about BCAA branched-chain amino acids, as well as synthesizing scientific evidence that contributes both to society and to the academic community. Objective: The objective defined for the mobilization of this study is to identify in the literature, from scientific evidence, the effectiveness of supplementation with branched-chain amino acids in the practice of physical activity. Methodology: To carry out this research, a literature study was carried out, based on surveys in scientific databases where information from different studies already published on the subject will be collected. Results and Discussions: BCAAs are present in supplementation. This option has been much sought after mainly by athletes who need more resources to effectively perform their goals according to the proposed physical activities. The indication of supplements vary according to each particularity and need of individuals. In this process, supplements have their composition of vitamins, minerals, amino acids, metabolites, herbs and botanicals, however, nutritional supplements cannot be considered a standard and conventional food in the daily diet. Each case deserves to be analyzed, because for the supplements to exert their effects, it is necessary for individuals to be physically active. Conclusion: During long-term exercise, BCAA supplementation has numerous benefits in terms of discomfort and fatigue resulting from exercise. This process occurs due to the consumption of these amino acids, generating a greater competition with tryptophan that produces the action of inhibition of central fatigue that, through serotonin, stimulates the neurotransmitters involved in the process.